(untitled) (Al-Academy, 2022)
The most important topics that constitute the aesthetic and substantive aspect of the theatrical performance represented by the spatial environment of the presentation and the proposed virtual place that contains the technical and artistic elements of the presentation and highlights the strength of influence on it. In light of the above, the researchers divided the topic into four chapters. The first chapter contained (the methodological framework), which included the research problem with regard to the directing treatments between the directors in establishing or creating theatrical venue, the importance of the research and the aim of the research, and the limits of the research to conclude the chapter by defining the terms. The second chapter (the theoretical framework) was divided into two sections that dealt with in the first topic: (the concept of theatrical place), while the second topic came under the title (directive experiences of employing the place in the world theater), and previous studies and the results of the theoretical framework. The third chapter contains (Research procedures) include the research sample, which is a play (Passport), the research community, the reason for selecting the sample and analyzing the sample. While the fourth and final chapter came with (results and conclusions), and included the recommendations suggested by the researchers, as well as the proposals, and contained a list of sources